AHP for the assessment of permafrost environment in muli mining area of Qinghai Province, China - Cao, Wei; Sheng, Yu; Qin, Yinghong (Cold Regions Engineering 2009, 2009)
Based on analyzing the interaction between coal mining and permafrost environment, an integrated indicator system for evaluating the permafrost environment of Muli mining area, a opencast coal mine located in Qinghai province, China, is proposed in this study. This system consists of three subsystems: permafrost freezing-thawing erosion sensibility, permafrost thermal stability and permafrost ecological fragility. The grade standard of environment assessment in this area, including five situations: ideal- (0.69∼1.00), good- (0.52∼0.69), general- (0.36∼0.52), bad- (0.23∼0.36) and worse-situation (0.00∼0.23), was established by loading indicators' weights, which were calculated using the Analytic Hierarchy Process (AHP). Based on this method, the permafrost environment in Muli mining area was evaluated according to documented literature and fieldwork data. The index of permafrost environment, by normalizing, is 0.46. The result indicates that although coal mining only experiences a short period until now, the permafrost environment in Muli mining area is in a general situation. It means that the permafrost environment has been destroyed to a certain degree by anthropologic activities and might be further degenerated. However, at this degree, a new equilibrium could be achieved if the current environmental system is maintained and treatments are constructed against further damages. Copyright ASCE 2009.